2019
DOI: 10.7774/cevr.2019.8.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Rhoptry antigens asToxoplasma gondiivaccine target

Abstract: Toxoplasmosis is a cosmopolitan zoonotic infection, caused by a unicellular protozoan parasite known as Toxoplasma gondii that belongs to the phylum Apicomplexa. It is estimated that over one-third of the world's population has been exposed and are latently infected with the parasite. In humans, toxoplasmosis is predominantly asymptomatic in immunocompetent persons, while among immunocompromised individuals may be cause severe and progressive complications with poor prognosis. Moreover, seronegative pregnant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 173 publications
0
31
0
Order By: Relevance
“…A universal vaccine should protect hosts, including humans, from acute invasion and congenital toxoplasmosis. Thus, the vaccine should reduce the incidence of infection in both farm animals meant for human consumption and cats responsible for oocyst shedding and environmental contamination with infectious forms of T. gondii, which, in turn, is expected to minimize parasite transmission to all hosts, including humans [21]. However, despite many years of research, the construction of an effective and universal anti-Toxoplasma vaccine for use in both humans and animals remains an elusive goal.…”
Section: Discussionmentioning
confidence: 99%
“…A universal vaccine should protect hosts, including humans, from acute invasion and congenital toxoplasmosis. Thus, the vaccine should reduce the incidence of infection in both farm animals meant for human consumption and cats responsible for oocyst shedding and environmental contamination with infectious forms of T. gondii, which, in turn, is expected to minimize parasite transmission to all hosts, including humans [21]. However, despite many years of research, the construction of an effective and universal anti-Toxoplasma vaccine for use in both humans and animals remains an elusive goal.…”
Section: Discussionmentioning
confidence: 99%
“…An effective human vaccine against T. gondii infection is currently unavailable. DNA, subunit or protein vaccines against T. gondii have been studied but were unsuccessful [3,4]. As such, finding novel vaccines that are highly effective against T. gondii in-fection remains a great challenge for researchers.…”
mentioning
confidence: 99%
“…In this study, we investigated the protective efficacy of T. gondii ROP13 vaccine generated in a virus-like particle form using ROP13, a protein secreted from the rhoptries which assists host cell invasion [4]. In this study, influenza VLPs expressing In general, memory B cells and plasma cells for specific antigens after immunization gradually decrease and are present at low levels.…”
mentioning
confidence: 99%
“…In recent years, genetically modified strains as vaccines have become a major research focus. Many scientists have begun to study genetically modified parasites, and the virulence of T. gondii was weakened by deleting certain genes, as has been achieved in some studies [18][19][20][21][22]. In addition, early studies have shown that T. gondii is a purine auxotroph organism [23,24].…”
Section: Introductionmentioning
confidence: 99%